Impact of Temporal Visual Flicker on Spatial Contrast Sensitivity in Myopia - Ye, Jie; Sinha, Pawan; Hou, Fang; He, Xianghang; Shen, Meixiao; Lu, Fan; Shao, Yilei (Frontiers in Neuroscience, 2021)
Purpose: To investigate whether short-term exposure to high temporal frequency full-field flicker has an impact on spatial visual acuity in individuals with varying degrees of myopia. Methods: Thirty subjects (evenly divided between control and experimental groups) underwent a five-minute exposure to full-field flicker. The flicker rate was lower than critical flicker frequency (CFF) for the experimental group (12.5 Hz) and significantly higher than CFF for the controls (60 Hz). Spatial contrast sensitivity function (CSF) was measured before and immediately after flicker exposure. We examined whether the post flicker CSF parameters were different from the pre-exposure CSF values in either of the subject groups. Additionally, we examined the relationship between the amount of CSF change from pre to post timepoints and the degree of subjects’ myopia. The CSF parameters included peak frequency, peak sensitivity, bandwidth, truncation, and area under log CSF (AULCSF). Results: There was no significant difference of all five pre-exposure CSF parameters between the two groups at baseline (P = 0.333 ~ 0.424). Experimental group subjects exhibited significant (P < 0.005) increases in peak sensitivity and AULCSF, when comparing post-exposure results to pre-exposure ones. Controls showed no such enhancements. Furthermore, the extent of these changes in the experimental group was correlated significantly with the participants’ refractive error (P = 0.005 and 0.018, respectively). Conclusions: Our data suggest that exposure to perceivable high-frequency flicker (but, not to supra-CFF frequencies) enhances important aspects of spatial contrast sensitivity, and these enhancements are correlated to the degree of myopia. This finding has implications for potential interventions for cases of modest myopia.